A interpretação de pistas prosódicas na aposição de atributos em sentenças ambíguas do PB (Revista de Estudos da Linguagem, 2007)
With the aim to investigate the prosodic cues influences in theinterpretation of ambiguous sentences that present a NP1 – VP –NP2 – ATTRIBUTE structure, as in “O pai visitou o filho embriagado”(“The drunk father visited the son” / “The father visited the drunk son”),some tests were applied to four subjects of an earlier experimentwhere they were invited to reinterpret their own reading aloud. Thesesubjects were also invited to produce another reading aloud, nowgiving explicit prosodic cues to indicate the attribute apposition – tothe NP1 or to the NP2. The attribute apposition of the earlier readingaloud and this re-reading were interpreted by other groups of subjects.We present here the results and analyses of this experiment.